The factors influencing financial stability of public service establishments of the population - N. V. Zhuravleva (Путеводитель предпринимателя)
In the article questions of financial stability of public service establishments of the population which depends on many internal and external factors rendering both a positive, and negative impact on their activities are considered. Financial stability of the entities of BONDS is influenced also by other factors, such as objective and subjective. Financial stability is considered within industry specifics of BONDS.